The feasibility of an innovative online mind-body wellness program for medical students - Christina Ray; Shankar Jha; Makayla Watt; Ashley Hyde; Kendra McGowan; Sarah Tymchuk; Puneeta Tandon (Canadian Medical Education Journal)
Purpose: Medical students have higher stress levels than their age-matched peers; however, few online wellness interventions have been trialed in this population. This pilot study examined the feasibility of an online wellness program for medical students.